NONLINEAR DIFFUSION IN SUPERCONDUCTORS - Urazov, Abduxoliq (Физико-технологического образование, 2025)
In this paper, the dynamics of magnetic flux penetration in a viscous flow regime is studied by analytically solving the nonlinear diffusion equation for the magnetic field induction. It was assumed that the applied external field is parallel to the sample surface. An exact solution of the nonlinear diffusion equation for the magnetic induction has been obtained using a well-known scaling method